Medieval Liège at the crossroads of Europe monastic society and culture 1000-1300 - Vanderputten, Steven 1976-; Snijders, Tjamke 1981-; Diehl, Jay (Medieval church studies, 2017)
This volume collects studies on the role of monastic institutions in the exchange of cultural and socio-economic capital in the medieval diocese of Liège. 0During the high Middle Ages, the bishopric of Liège found itself at a cultural crossroads between the German Empire and the French lordships. The Liègeois themselves summed up the situation when they declared that: 'Gaul considers us its most distant inhabitants, Germany as nearby citizens. In fact we are neither, but both at the same time'. This same complexity is also echoed by present-day historians, who have described Liège as a hub of interactions between two great civilisations. Medieval monastic communities in Liège were key sites of this exchange, actively participating in the cultural developments, social networks, and political structures of both regions. 0Bringing together the work of international scholars, this collection of essays addresses the problem of monastic identity and its formation in a region that was geographically wedged between two major competing socio-political powers. It investigates how monastic communities negotiated the uncertainties of this situation, while also capitalizing on the opportunities it presented. As such, this book sheds light on the agency of monastic identity formation in a small but complex region caught at the crossroads of two major powers